Analysis of The Influence of F.O Purifier Maintenance on The Performance of The Main Engine on The KM. Logistik Nusantara 2 Ship - Satrio Wibowo Ajie; Antonius Edy Kristiyono; Teguh Pribadi; Nasri; Rama Syahputra Simatupang; Imam Sutrisno (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The performance of a diesel engine is greatly influenced by fuel. Diesel engines really need clean fuel so that engine combustion is maximized. Many companies today prefer fuel oil because it is cheaper than other fuels but fuel oil is still contained by water, mud and dirt so it requires a purifier aircraft to separate the fuel from these impurities. The purpose of this study is to find out how the results of diesel engine combustion are if maintenance is carried out on the purifier periodically. This research method uses descriptive qualitative. The data source was obtained directly by means of observation and documentation as well as literature related to this research which was carried out during the sea project for 12 months at KM. Logistik Nusantara 2 ship.